2008
DOI: 10.1001/archpsyc.65.10.1176
|View full text |Cite
|
Sign up to set email alerts
|

Neural Response to Self- and Other Referential Praise and Criticism in Generalized Social Phobia

Abstract: Context Generalized social phobia (GSP) is characterized by fear/avoidance of social situations. Previous studies have examined the neural responses in GSP to one class of social stimuli, facial expressions. However, studies have not examined the neural response in GSP to another equally important class of social stimuli, the communication of praise or criticism. Objective To examine the neural response to receipt of praise or criticism in GSP; specifically, to determine whether patients with GSP show an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
126
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(136 citation statements)
references
References 43 publications
8
126
1
Order By: Relevance
“…Such association fits well also with data on patients with generalized social phobia displaying stronger connectivity between amygdala and dorsomedial PFC than controls during self-referential criticism (51). Similarly, more neurotic individual shows greater connectivity between right amygdala and right dmPFC when processing angry and fearful compared to neutral faces (52).…”
Section: Discussionsupporting
confidence: 87%
“…Such association fits well also with data on patients with generalized social phobia displaying stronger connectivity between amygdala and dorsomedial PFC than controls during self-referential criticism (51). Similarly, more neurotic individual shows greater connectivity between right amygdala and right dmPFC when processing angry and fearful compared to neutral faces (52).…”
Section: Discussionsupporting
confidence: 87%
“…Ventrolateral prefrontal cortex activation also differed significantly for anxious versus healthy adolescents. Further evidence has suggested that the medial prefrontal cortex, involved in representation of the self (e.g., self-criticism) may be related to SP symptoms (Blair et al 2008).…”
Section: Neuroimaging and Genetic Bases Of Behavior Impairmentsmentioning
confidence: 99%
“…This thesis also adds to the notion that heightened fear-related neural response to selfreferential criticism is an indicator of SAD (Blair et al, 2008a;Blair et al, 2008b). This information-processing deficit is also highlighted in the psychological literature stressing that attention towards the self is an important factor maintaining the disorder (Clark & McManus, 2002;Clark & Wells, 1995;Mansell & Clark, 1999;Mansell et al, 2003).…”
Section: Targeting the Fear Circuitrymentioning
confidence: 70%
“…For instance, Costafreda and colleagues conducted a meta-analysis of 385 neuroimaging studies and found that tasks including emotional faces are a strong predictor of amygdala responsivity (Costafreda, Brammer, David, & Fu, 2008). Secondly, neural response to self-referential criticism was evaluated using a disorder-relevant paradigm developed by Dr Karina Blair and colleagues (Blair et al, 2008a) that was translated into Swedish (see also Figure 3). The sentences were split into three categories based on the referential target: self, other female, or other male.…”
Section: Experimental Tasksmentioning
confidence: 99%